Information Technology Integration in Kitab Kuning Instruction at Traditional Dayah in Aceh: Tengku Perceptions, Adaptive Strategies, and Implementation Challenges - Daysra abrar; Syabuddin Syabuddin; Saiful Saiful; Zulfatmi Zulfatmi; Hayati Hayati (Attractive : Innovative Education Journal, 2026)
The integration of information technology (IT) into traditional Islamic education has become a major challenge in Indonesia’s pesantren reform discourse. Traditional dayah in Aceh, recognized as some of the oldest Islamic educational institutions in the archipelago, face a dual imperative: preserving classical scholarly traditions centered on kitab kuning while responding to rapid educational digitalization. This study aims to (1) examine tengku perceptions of IT integration in kitab kuning instruction, (2) analyze the adaptation strategies they employ, and (3) identify key implementation challenges. A qualitative multiple-case study was conducted at three traditional dayah in Aceh: Dayah Najmul Hidayah Al-Aziziyah Batee Iliek (Bireuen), Dayah Anwarul Munawwarah Kuta Krueng (Pidie Jaya), and Dayah Darussalam Lampoh Tuah (Pidie). Data were collected through semi-structured interviews with six tengku and participant observation, then analyzed using the Miles, Huberman, and Saldana interactive model through open, axial, and selective coding with source and technique triangulation. Findings reveal that tengku perceptions are adaptive-selective, guided by fiqhiyah considerations balancing mashlahah (benefit) and mafsadah (harm), rather than absolute acceptance or rejection of technology. IT practices include the use of Maktabah Syamilah, YouTube, Zoom, and TikTok/Facebook live-streaming for da‘wah, while halaqah and sorogan remain central pedagogical methods. A digital literacy gap between senior and junior tengku has produced a technology delegation mechanism based on scholarly authority hierarchies, extending the Technology Acceptance Model (TAM). Major challenges include unstable infrastructure, limited digital literacy among senior tengku, and the absence of formal IT governance policies.